KOMPARASI SYARAT KEABSAHAN “SEBAB YANG HALAL” DALAM PERJANJIAN KONVENSIONAL DAN PERJANJIAN SYARIAH - Tri Wahyu Surya Lestari; Lukman Santoso (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Social relation is a basic need for human beings in the society. Since members of the society are coming from various backgrounds, there should be rules or regulations to be followed by the members of the society. The rules aim at creating safety and comfort in the society and also maintaining a good and harmonious social relation. One of the rules is agreement. There are 3 sub-systems of law in Indonesia i.e. Western Law, Customary Law and Islamic Law. Prior to an agreement, there are requirements needed to be fulfilled so the agreement can be effective as a rule. One of the requirements is “legal cause” which should be studied further by each side due to some differences in conventional agreement and agreement based on Islamic Law in order to prevent unnecessary misunderstanding.